The Problems and Countermeasures in the Promotion of Reading in University Libraries - Li, Junjie (Journal of Theory and Practice of Social Science, 2023)
With the rapid development of modern society and the highly developed internet technology, it has changed people's traditional way of acquiring knowledge and also expanded the connotation and extension of reading. It can be said that reading exists everywhere in today's society. The current reading promotion work is not only carried out by libraries. The vigorously promoting and popularizing electronic reading materials poses a serious threat to traditional reading methods, which not only facilitates reading methods but also impacts people's thinking. So universities need to vigorously promote library reading. This article mainly studies the problems and countermeasures in the promotion of reading in university libraries. I hope to provide useful suggestions.